Republic Of Estonia : Republic Of Estonia Second Review Under the Stand-by Arrangement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
The fast economic recovery despite a strong fiscal correction is a result of the government's determined macroeconomic and structural policies. Executive Directors commend the government for adhering to its ambitious fiscal targets. The careful crafting of legislation to establish a second pillar of the pension system is appropriate. The high confidence in the currency board and the strengthening of the banking system will stabilize the financial system. Nonbanking supervision has to be strengthened further and the draft securities market law should be implemented.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet